Synthesis and Biological Activity of New Heterocyclic Compounds Derived from Vanillin, Acetone and Thiosemicarbazide - AL-Aqil, Amjad Abdulbaqi Mohammed; Maresh, Mohammed Fahd Naif; Ali, Motaz Sadeq Mohammed; Saeed, Aiman Adel Mohammed; AL-Ghaili, Amr Khaled Hamood; Mohammed, Morsal Ali Ahmed (University of Science and Technology, Sana’a, 2026)
This study included synthesized was a series of new heterocyclic compounds derivatives such as: Pyrazole (4a-c, 4h), Oxazine (4e), Thiazine (4f), Isoxazole (4d), thiazolidine-4-one (4hh), pyrazolo-thiazole (4hhhh) and pyrimidine (4ee & 4ff), Tetrazoles (1a), imidazolidine-4-one (1b, 1c), 4-thiazolidinones (1d), 1,3-Oxazepine (1e), Quinazoline or Hydroquinazoline (1f), Oxazolidines (1g and 1h) derivatives. All chemical reactions to preparation of the compounds under study were investigated by using TLC technique; the physical properties of the prepared compounds were also studied. This work is divided into two parts:- Part one: The first step includes preparation of chalcone (4) from condensation reaction of one mole Vanillin (2) with tow moles of acetone (1 & 3) in base medium which cyclized by react with deferent compounds (urea, thiourea, hydrazine hydrate, phenylhydrazine, 2,4-dinitrophenylhydrazine, thiosemicarbazide and hydroxylamine hydrochloride) in alcoholic sodium hydroxide NaOH to produce (Pyrazole 4a-c, 4h, Oxazine 4e, Thiazen 4f, and Isoxazole 4d) derivatives, respectively, and in presence of glacial acetic acid react Chalcone (8) with (urea and thiourea) formed new pyrimidine (4ee & 4ff) derivatives. Chalcone (8) was reflexed on cyclocondensation with malononitrile afforded corresponding Pyridine (4g) derivatives. Pyrazole (4h) was reflexed with chloroacetic acid to produce thiazolidine-4-one derivatives (4hh) which reacted with p-dimethylaminobenzaldahyde to give compound (4hh) followed by the cyclized by using hydrazine hydride to give pyrazolo–thiazole derivation (4hhhh) and as shown in the first track diagram. Part two: The first step includes preparation of Schiff base (1) from reaction of Vanillin with Thiosemicarbazide in acid medium which cyclized by react with (Sodium Azide, amino acid (Glycine), Mercaptoacetic acid (thioglycolic acid), phthalic anhydride, 2-Aminobenzoic acid, hydroxyacetic acid (Glycolic acid) and Lactic acid afforded the substituted heterocyclic (Tetrazoles (1a), imidazolidine-4-one (1b, 1c), 4-thiazolidinones (1d), 1,3-Oxazepine (1e), Quinazoline or Hydroquinazoline (1f), Oxazolidines (1g and 1h)) derivatives, respectively. 1,3-Diazepine-4,7-dione compounds (1ee) were prepared from the reaction of phenylhydrazine with 1,3-Oxazepine-4,7-dione (1e) and as shown in the second track diagram. All chemical reactions to preparation of the compounds under study were investigated by using TLC technique, The physical properties of the prepared compounds were also studied. The final products were screened for their antimicrobial and antioxidant activities. The synthesized derivatives were evaluated for their antimicrobial activity against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli and K. pneumonia) bacteria, and their antifungal activity against Candida albicans fungus, the results showed that tested compound (4hhhh) showed the highest and promising antibacterial activity against E. col bacteria. Also, the antioxidant activity of the synthesized compounds was evaluated by Ferric-bipyridine reducing capacity of total antioxidants (FBRC) method. The results showed that the compounds (4hhhh and 1g) to possess very strong antioxidant activity better than another prepared compounds.